ANALISIS PEMBUATAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI CAMTASIA DAN WONDERSHARE FILMORA DALAM PEMBELAJARAN ONLINE PADA SMK AR-RAHMAN MEDAN - rikky simanjuntak; Muhammad Daliani; Nilam Sari; Vera Ompusunggu (JURNAL CURERE, 2021)
Based on the Circular from the Minister of Education and Culture Number: 36962/MPK.A/HK/2020 dated March 17, 2020 regarding "Online Learning and Working from Home in the context of Preventing the Spread of Corona Virus Disease (Covid-19)", then SMK Ar Rahman carry out learning by using applications from the internet, namely Google Classroom. The making of learning videos was suggested by several network computer engineering teachers using the Camtasia and Wondershare Filmora applications. Camtasia and Filmora are applications that are used to edit videos. Learning videos that are intended to make it easier for students to understand the subject matter are not always in accordance with the needs and desires of students. The research used is a type of qualitative descriptive research. The data collection technique was obtained from interviews from the results of socialization, documentation and questionnaires (questionnaires). The research subjects consisted of 20 subject teachers. The temporary hypothesis is that it shows that the Wondershare Filmora video making design is better but only experienced editing and used to using the application. However, for subject teachers who are beginners, Camtasia seems easier and easier to use.